2020
DOI: 10.1371/journal.pone.0234006
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of depressed mood in immigrants’ offspring reflects their social conditions in the host country: The HELIUS study

Abstract: Background Immigrants from low-and middle-income countries who have settled in high-income countries show higher risks of depression in comparison with host populations. The risks are associated with adverse social conditions. Indecisive results have been reported on the depression risks of the offspring of immigrant populations. Objective To assess the prevalence of depressed mood in immigrant offspring relative to the host population and to analyse whether that risk is explained by social conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that, more recently, the Hispanic paradox literature has expanded on theories beyond generation status, the Salmon Bias, or Selective Theory that impact whether or not immigrants experience negative physical or mental health outcomes, particularly analyzing the role of resilience (Kroenke, Spitzer, Williams, Monahan, & Löwe, 2007 ; Gonzalez-Guarda, Stafford, Nagy, Befus, & Conklin, 2020 ; Kroenke et al, 2009 ). It is necessary to highlight that the Latinx community is resilient and upholds many cultural values as strengths, rather than deficits (Stronks et al, 2020 ; Foo et al, 2018 ). Providers should emphasize these protective factors by adapting interventions to include relevant cultural values supported in the research literature, such as integration of family into care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, more recently, the Hispanic paradox literature has expanded on theories beyond generation status, the Salmon Bias, or Selective Theory that impact whether or not immigrants experience negative physical or mental health outcomes, particularly analyzing the role of resilience (Kroenke, Spitzer, Williams, Monahan, & Löwe, 2007 ; Gonzalez-Guarda, Stafford, Nagy, Befus, & Conklin, 2020 ; Kroenke et al, 2009 ). It is necessary to highlight that the Latinx community is resilient and upholds many cultural values as strengths, rather than deficits (Stronks et al, 2020 ; Foo et al, 2018 ). Providers should emphasize these protective factors by adapting interventions to include relevant cultural values supported in the research literature, such as integration of family into care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified both ethnic discrimination and individuals' socio-economic position as key risk factors for depressive symptoms in ethnic minorities (Sempértegui et al, 2023;Stronks et al, 2020;Williams, Yu, Jackson, & Anderson, 1997). Perceived ethnic discrimination (PED)-which encompasses both overt and subtle indignities attributed to one's ethnic background-is positively associated with depressed mood and major depressive disorder (Wallace, Nazroo, & Bécares, 2016).…”
Section: Individual and Neighborhood Determinants Of Depressive Sympt...mentioning
confidence: 99%
“…We already mentioned various economic and possible cultural factors that cause people with a non-Western migration background to be more exposed to the risk of infection, which can lead to more anxiety and stress. In fact, research by Stronks et al ( 2020 ) showed that the chance of depression is twice or even three times as high among Dutch people with Surinamese, Turkish, and Moroccan background as it is among Dutch people without a migration background, although these differences are partly due to differences in social status between the various population groups.…”
Section: Literature Review: Social Class Social Capital and The Menta...mentioning
confidence: 99%